ANALISA PENGARUH BRAND EQUITY TERHADAP KEPUTUSAN PELANGGAN MEMBELI SEMEN PT. SEMEN BATURAJA PADA MASYARAKAT PALEMBANG - A NAZARUDDIN .; M FIKRI RIDHA PUTRA (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2013)
This research aims at knowing the effects of the elements of brand equity, which consists of brand awareness, perceived quality and brand loyalty on the costumers’ decision to buy the product of Semen Baturaja. This research is based on the condition where the need for cement increasing that has made high competition among firms in the industry. Of the total cement industry, PT Semen Baturaja has a low market share which accounts for only 2,2 percent. However, Semen Baturaja has become a market leader in South Sumatera, especially in Palembang city. Theoretically, the condition can be induced by strong brand equity of the firm’s product.This research is based on multiple linear regression analysis by using SPSS 16.0 program. The regression analysis has resulted in an estimate of the decision function, Y = 3.001 + 0.402X1 + 0.439X3. The result shows that the variable brand awareness (X1) and brand loyalty (X3) have significant positive effect on the consumers’ decision. The variable brand loyalty has more dominant effect than brand awareness on the buying decision for Semen Baturaja with coefficient of 0.439. Based on the result of t-test, both brand awareness and brand loyalty have significant effect, but the variable perceived quality has no significant effect on the costumers’decision. Coefficient Adjusted R2 of 0.596 shows that the independen variables influence the costumers’ buying decision by 59.6%, while the rest is influenced by other variables beyond this research